International perspectives on the strengthening of impact assessment through integration and focus - Retief, F.; Bond, A.; Gunn, J.; Pope, Jennifer; Morrison-Saunders, A. (Taylor & Francis, 2014)
This paper consolidates international responses to the argument that there is a need to strengthen impact assessment (IA) through greater integration and focus. It is based on invited reflections by various international authors in the field of IA. The main conclusions are that power and context are important underlying reasons for the diversity of IA types; that in certain instances IA legislation works against achieving integration and focus; and that there is a pressing need to be able to measure and demonstrate added value and effectiveness in practice. The paper concludes by setting a research agenda reflecting the need to better understand why diversity exists in IA, what stakeholders expect from the process and how to improve practice based on greater understanding of what the various types of IA deliver.